Isolasi, Karakterisasi dan Identifikasi Bacillus spp Berasosiasi Abalon (Haliotis asinina) - rahman, fatur (Samota Journal of Biological Sciences, 2022)
Microbiota associated with animals provide benefits for the health and growth of the animal concerned. This study aims to isolate, characterize and identify Bacillus spp. associated with abalone as a probiotic candidate. Characterization and identification were based on morphological, physiological and biochemical characters using a microbiology analyzer. The results of isolation from the shell and digestive tract of abalone obtained 4 isolates of Bacillus which had different morphological characteristics. characterization and identification studies showed that isolates CAK1 and CAK2 were Bacillus coagulans with 94% and 99% similarity, respectively, SLK2 isolates were Bacillus licheniformis with 99% similarity, and SLK1 was Bacillus pumilus with 99% similarity